Differences in Gait and Stair Ascent After Total Ankle Arthroplasty and Ankle Arthrodesis. (March 2021) - Sanders, Austin E.; Kraszewski, Andrew P.; Ellis, Scott J.; Queen, Robin; Backus, Sherry I.; Hillstrom, Howard; Demetracopoulos, Constantine A.
Background: Ankle arthrodesis has historically been the standard of care for end-stage ankle arthritis; however, total ankle arthroplasty (TAA) is considered a reliable alternative. Our objective was to compare 3-dimensional foot and ankle kinetics and kinematics and determine the ankle power that is generated during level walking and stair ascent between TAA and ankle arthrodesis patients. Methods: Ten patients who underwent TAA with a modern fixed-bearing ankle prosthesis and 10 patients who previously underwent ankle arthrodesis were recruited. Patients were matched for age, sex, body mass index, time from surgery, and preoperative diagnosis. A minimum of 2-year follow-up was required. Patients completed instrumented 3D motion analysis while walking over level ground and during stair ascent. Between-group differences were assessed with a 2-tailed Mann-Whitney exact test for 2 independent samples. Results: Sagittal ankle range of motion (ROM) was significantly higher in the TAA group (21.1 vs 14.7 degrees, P = .003) during level walking. In addition, forefoot-tibia motion (25.3±5.9 degrees vs 18.6±5.1 degrees, P = .015) and hindfoot-tibia motion (15.4±3.2 degrees vs 12.2±2.5 degrees, P = .022) were significantly greater in the TAA group. During stair ascent, sagittal ankle ROM (25 vs 17.1 degrees, P = .026), forefoot-tibia motion (27.6 vs 19.6 degrees, P = .017), and hindfoot-tibia motion (16.8 vs 12 degrees, P = .012) was greater. Conclusion: There were significant differences during level walking and stair ascent between patients with TAA and ankle arthrodesis. TAA patients generated greater peak plantarflexion power and sagittal motion within the foot and ankle compared to patients with an ankle arthrodesis. Further investigation should continue to assess biomechanical differences in the foot and ankle during additional activities of daily living. Level of Evidence: Level III, comparative study.